Formulasi soft cookies ubi jalar ungu (Ipomoea batatas (L.) Lam.) dengan pemanis stevia terhadap uji hedonik, karakteristik warna, dan kandungan gizi - Sulistyawati, Putri; Sugiyanti, Dina; Hardiansyah, Angga (Poltekkes Kemenkes Aceh, 2026)
Background: Cookies are among the most widely consumed snack products in Indonesia, with consumption growing at 4,25% every year. However, the high sugar content in conventional cookies has driven the demand for innovations using local ingredients and alternative sweeteners. Purple sweet potato is rich in nutrients and anthocyanins, while stevia provides sweetness 200-300 times sucrose without calories. This study integrated soft cookies using purple sweet potato puree with stevia covering hedonic testing, color characteristics, and nutritional content.Objectives: To analyze the effects of purple sweet potato soft cookies formulated with stevia on hedonic testing, color characteristics, and nutritional content. Methods: An experimental study with a completely randomized design (CRD), three formulations, and three replications (nine experimental units) was conducted. Hedonic testing was performed by 30 untrained panelist using scale 1-6. The color was measured using a chromameter. Proximate analysis was performed according to the AOAC (2005): moisture (gravimetric), ash (dry ashing), protein (Kjeldahl), fat (Soxhlet), carbohydrate (by difference), and energy (Atwater factor). Hedonic data were analyzed using Kruskal-Wallis test, and color and nutritional data using one-way analysis ANOVA (α=0.05).Results: The hedonic parameters of color, taste, texture, and overall acceptability differed significantly (p<0,05), whereas aroma showed no significant difference (p>0,05). All color parameters differed significantly (p<0,05). Moisture, protein, fat, carbohydrate, and energy content differed significantly (P<0,05). The moisture content of all formulations and the ash content of F2 exceeded the SNI 2973:2011 standard, while the protein, fat, carbohydrate, and energy content met the SNI standards. Conclusion: F3 (80%puree) demonstrated the best acceptability in terms of color, taste, texture, and overall acceptance, although it had the highest moisture and lowest protein content.